JARINGAN SOSIAL PENAMPUNG BARANG BEKAS DI KELURAHAN LABUH BARU BARAT KECAMATAN PAYUNG SEKAKI KOTA PEKANBARU - Siregar, Andi; ", Indrawati (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
This research was conducted in Labuh Baru Barat Sub District, Payung Sekaki District, Pekanbaru City. Issues of the research are (1) how the social network forms between scavenger, used containers, and factory agent? (2) what factors influence the closeness of relationships in social network between scavengers and container used goods and container used goods with factory agent? The purpose of researc is to determine the form of social networks that occur between scavengers, container used goods, and factory agent. To find out the relationship of closeness that occurs between scavengers with container use goods and container use goods with factory agent. The sample determination technique was determined by purposive sampling because the author had determined a number of subject criteria to be carried out as many as 5 second hand containers and 5 scavengers. The author uses qualitative research conducted by the author is descriptive qualitative research with data collection technique namely observation, interviews, documentation, and literature study. The type of research conducted by author is descriptive qualitative research. The result from field say that the form of a social network that holds used goods in Labuh Baru Barat Sub District of Payung Sekaki District is a horizontal and vertical network. The form of attachment in social network is the production relationship, relationship between accounts receivable debt, personal relationships, relationship in freight forwarding, payment relationship, hospitality relationship, and solidarity in used goods collection.Keyword: Social Network, Second Hand Container